Delayed diagnosis of anorectal malformations in neonates. Issue 10 (26th August 2019) - Kruger, Paul; Teague, Warwick J.; Khanal, Rija; Hutson, John M.; King, Sebastian K.
Abstract : Background: Anorectal malformations (ARM) are common congenital abnormalities of the terminal hindgut. Ideally, ARM should be diagnosed at, or shortly following, birth by careful physical examination of the perineum. Delayed diagnosis has been implicated as a risk factor for complications, including intestinal perforation. This study aimed to determine the rate of delayed diagnosis and associated intestinal perforation in ARM. Methods: A retrospective review was performed for all ARM patients managed at The Royal Children's Hospital over a 16‐year period (2000–2015). Data collected included ARM type, timing of diagnosis and complications. Delayed diagnosis was defined as being at more than 24 h of age. Results: A total of 243 ARM patients (male 146/243, 60%) were included. The most frequent ARM types were perineal fistula (83/243, 34%) and rectovestibular fistula (40/243, 16%). Diagnosis was delayed beyond 24 h of age in 92 of 243 (38%) patients. The ARM type most commonly delayed in diagnosis was perineal fistula (37/83, 45%). Two patients in whom diagnosis was delayed suffered an intestinal perforation. Conclusion: Delayed diagnosis in ARM patients remains a common, and potentially fatal, occurrence. Improved assessment of newborns is required to ensure timely diagnosis of ARM, and avoidance of complications associated with delayed diagnosis. Abstract : Anorectal malformations are a common cause of intestinal obstruction in newborns. Often the diagnosis is missed in the first 24 h, leading to potential complications, including intestinal perforation. We have reviewed more than 240 cases of anorectal malformations to highlight the factors that lead to a missed diagnosis.